Antibacterial Inhibitor as an Expired Metoclopramide in 0.5M Phosphoric Acid - Anaee, Rana Afif; Abd Al-Majeed, Majed Hameed; Naser, Shaimaa Alaa; Kathem, Mustafa M.; Ahmed, Omer Akram (Al-Khwarizmi Engineering Journal, 2019)
Expired drug Metoclopramide was investigated as an antibacterial corrosion inhibitor for carbon steel in 0.5M H3PO4 solution using the electrochemical method at 30oC and 60oC. The results showed that this drug is an efficient inhibitor for carbon steel and the efficiency reached to 82.244 % for 175 ppm at 30oC and 76.146% for 225 ppm at 60oC. The adsorption of drug on carbon steel surface follows Langmuir adsorption isotherm with small values of adsorption-desorption constant. The polarization plots revealed that Metoclopramide acts as mixed-type inhibitor. Some parameters of inhibition process were calculated and discussed. The surface morphology of the carbon steel specimens was analyzed using scanning electron microscope and energy dispersive X-ray analysis. Antibacterial activity of inhibitor was also tested. Fourier-transform infrared (FTIR) spectroscopy confirmed the inhibitive role of Metoclopramide drug.